2012
DOI: 10.1111/j.1365-2702.2012.04288.x
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of the numeric pain rating scale in older postoperative patients

Abstract: Nurses should not rely solely on the NRS score in determining pain treatment; they need to communicate with older patients about their pain, the need for analgesics and eventual misconceptions about analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 22 publications
0
32
0
4
Order By: Relevance
“…Effective pain management of emergency department (ED) patients with bone fractures is not only a crucial element in patient satisfaction, but it is also a priority for providers and nurses because unrelieved pain can lead to adverse physical and psychological consequences (van Dijk, Kappen, van Wijck, Kalkman & Schuurmans, 2012). A seven year national survey published in the Annals of Emergency Medicine in 2012 concluded that patients 75 years or older who presented to EDs with a complaint of pain were 19% less likely to receive pain medication when compared to younger adults with similar injuries (Platts-Mills et all., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective pain management of emergency department (ED) patients with bone fractures is not only a crucial element in patient satisfaction, but it is also a priority for providers and nurses because unrelieved pain can lead to adverse physical and psychological consequences (van Dijk, Kappen, van Wijck, Kalkman & Schuurmans, 2012). A seven year national survey published in the Annals of Emergency Medicine in 2012 concluded that patients 75 years or older who presented to EDs with a complaint of pain were 19% less likely to receive pain medication when compared to younger adults with similar injuries (Platts-Mills et all., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Assessing pain and encouraging patients to report pain is essential because unrelieved pain can lead to adverse physical and psychological consequences (van Dijk, Kappen, van Wijck, Kalkman, & Schuurmans, 2012). According to the geriatricpain.org website "Pain is always subjective.…”
Section: Pain Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…13-15 The NRS should not be used alone, particularly in advanced age when the ability to appropriately use the NRS decreases; rather a combination of scales such as the VDS with the NRS is recommended. 16-17 …”
Section: Step 3: Measure Pain Intensity Using a Valid Reliable And mentioning
confidence: 99%
“…One-third of older adults reported postoperative pain as “painful but bearable” with a NRS of 5/10, 17 while nearly 53% of older adults have reported bothersome pain. 18 Older adults may state, “I can stand the pain, it's not that bad,” then refuse pain medications.…”
Section: Step 4: Assess the Tolerability Of Painmentioning
confidence: 99%